Graft failure after "ex-vivo" T-cell depleted haploidentical transplantation in pediatric patients with high-risk hematological malignancies. A risk factors and outcomes analysis. Issue 13 (10th November 2021) - Diaz, Miguel A.; Lopez, Ivan; Molina, Blanca; Pereto, Alba; Zubicaray, Josune; Sevilla, Julian; Castillo, Ana; Alenda, Raquel; Moreno, Miguel A.; Vicario, Jose Luis; González-Vicent, Marta
Abstract: Risk factors and outcomes of GF after TCD haploidentical transplantation in children with hematological malignancies were analyzed. 148 TCD transplants were included. 78 patients were diagnosed of ALL and 70 patients of AML. 22 out of 148 patients developed GF. MVA showed that patient <9 years (HR: 5.0; 95% CI: 1.1–23.0; p  = 0.03) and pre-transplant CD8+ ≥150/µL (HR: 12.0; 95% CI: 1.6–95.3; p  = 0.01) were associated with GF. A score was assigned to each patient. The cumulative incidence of GF for patients with CD8+ ≥150/µL (2 points) was 6 ± 4% and 3 ± 2% for patients <9 years (1 point) while for patients with 3 points was 24 ± 6%, With a median follow-up of 48 months (range; 4–180 months), 14 (64%) of 22 patients with GF are alive and disease-free. DFS for GF patients was 53 ± 12%. In conclusion, patient age and pre-transplant CD3+/CD8+ are associated with GF in children undergoing TCD haploidentical transplantation.